3.6: High‐Reliability OLED Display Panel using Top Gate IGZO TFTs for 55inch UHD TVs. (4th October 2019) - Huang, Yongchao; Cheng, Jun; Fang, Jingang; Ding, Luke; Zhao, Ce; Zhou, Bin; Wang, Dongfang; Yan, Liangchen
Abstract : To improve electrical characteristics of top gate a‐IGZO TFT we have been optimized the oxygen in IGZO layer and decreased the excess oxygen of Gate Insulator layer. We achieved that the uniformity of threshold voltages of a‐IGZO TFTs on Gen. 8.5 glass is approximately 0.61V. Also, we achieved BTS characteristic about Δ0.1V at 2hr PBTS and Δ‐0.2V at 2hr NBTiS. In addition, we demonstrated the 55‐in 4K UHD OLED TV with high reliability Image sticking.